Significant Role of Labour Migration in Global World. Case of Asia - Orłowska, Renata (Znacząca rola migracji zasobów pracy w globalnym świecie (na przykładzie Azji), 2010)
Every year, more than 5 million people crosses the borders of a country and seeks a more developed area. One of the most significant characteristics of today's global job market is occurring on a large scale cross-border migration. It is also a key element accompanying the processes of globalization. The first decade of the 21st century has confirmed this trend, stating at that the dynamic and significant development of economic migration. Important and significant contribution to the global migration has Asia-Pacific Region, where the scale of the flows of labour force has significantly increased in recent years. Annually about 400 thousand of Asians emigrate to North America, Australia and New Zealand. Especially large is the movement of highly skilled workers, which confirms the general trend in the world.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 163-172
Keywords: labour migration; migration in Asia; remittances